NASC-seq monitors RNA synthesis in single cells - Hendriks, Gert-Jan; Jung, Lisa A.; Larsson, Anton J. M.; Lidschreiber, Michael; Andersson Forsman, Oscar; Lidschreiber, Katja; Cramer, Patrick; Sandberg, Rickard (Nature communications, 2019)
Sequencing of newly synthesised RNA can monitor transcriptional dynamics with great sensitivity and high temporal resolution, but is currently restricted to populations of cells. Here, we develop new transcriptome alkylation-dependent single-cell RNA sequencing (NASC-seq), to monitor newly synthesised and pre-existing RNA simultaneously in single cells. We validate the method on pre-labelled RNA, and by demonstrating that more newly synthesised RNA was detected for genes with known high mRNA turnover. Monitoring RNA synthesis during Jurkat T-cell activation with NASC-seq reveals both rapidly up- and down-regulated genes, and that induced genes are almost exclusively detected as newly transcribed. Moreover, the newly synthesised and pre-existing transcriptomes after T-cell activation are distinct, confirming that NASC-seq simultaneously measures gene expression corresponding to two time points in single cells. Altogether, NASC-seq enables precise temporal monitoring of RNA synthesis at single-cell resolution during homoeostasis, perturbation responses and cellular differentiation. Sequencing of newly synthesised RNA can reveal the transcriptional dynamics in a population of cells. Here the authors develop NASC-seq to bring this sensitivity and temporal resolution to single-cell analysis.